PENERAPAN TEKNIK DIGITAL PRINTING DAN BORDIR DENGAN INSPIRASI BANGUNAN HOTEL SAVOY HOMANN BANDUNG UNTUK PRODUK FESYEN - Deanita Nabilla Fernanda; Widia Nur Utami Bastaman (Universitas PGRI Adi Buana Surabaya, 2019)
Buildings are one of the major inspiration frequently used on design theme for fashion industries.The purpose of this research is to raise the potential of a functional historical building in Bandungby the name of Hotel Savoy Homann. The visual potential of Hotel Savoy was used as inspirationfor fashion products in the form of women's clothing. To represent the value of Hotel SavoyHomann, the writer choosed to use two varieties of surface design techniques which is digitalprinting and embroidery. This research carried out the qualitative method by doing field observationand collecting data from related literature studies. The execution was in the form of explorationsketches from images inspired by the exterior design of Hotel Savoy Homann. The outcomeof this research is the application of digital printing and embroidery techniques on fashionproducts inspired by the building design of Hotel Savoy Homann Bandung whichprovidesfurther alternative choices for fashion products in women's clothing and acquaint Hotel SavoyHamman to citizens of Bandung.